2018
DOI: 10.1111/jpc.14079
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐economic composition of low‐acuity paediatric presentation at a regional hospital emergency department

Abstract: These findings demonstrate that a significant proportion of paediatric ED visits are of low acuity and that these visits yield a substantial cost to the health system. Further research is required regarding care givers' rationale and potentially other reasons underlying these low-acuity ED presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 26 publications
0
17
3
Order By: Relevance
“…A detailed analysis of the emergency department triage scores showed non-urgent visits to be frequent with over 80% in asylum-seeking children. This proportion is considerably higher than in previous reports of 30-40% of non-urgent visits in pediatric emergency care centers in Canada and Australia [19,34], 40% in Belgium and Italy [35,36] and 60% in the United States [37] . However, the tendency to provide primary care by tertiary health care institutions is described as global problem and one reason for growing health expenses [20].…”
Section: Discussioncontrasting
confidence: 61%
“…A detailed analysis of the emergency department triage scores showed non-urgent visits to be frequent with over 80% in asylum-seeking children. This proportion is considerably higher than in previous reports of 30-40% of non-urgent visits in pediatric emergency care centers in Canada and Australia [19,34], 40% in Belgium and Italy [35,36] and 60% in the United States [37] . However, the tendency to provide primary care by tertiary health care institutions is described as global problem and one reason for growing health expenses [20].…”
Section: Discussioncontrasting
confidence: 61%
“…[9][10][11][12][13] In contrast, in Queensland Australia, Williams et al 14 found that although presentations at a major metropolitan paediatric hospital ED were multifactorial, socio-economic factors did not contribute to the presentations. Although Alele et al 15 reported on a large data set collected over a 4-year period in Cairns, Queensland, families of very high socioeconomic status (SES) were 'twice as likely' to have a low acuity presentation to the hospital ED, compared with low SES families. Both Williams et al 14 and Alele et al 15 used the Australian Bureau of Statistics Socio-Economic Indexes for Areas (SEIFA) data and postcode as a means of indicating SES.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…Although Alele et al 15 reported on a large data set collected over a 4-year period in Cairns, Queensland, families of very high socioeconomic status (SES) were 'twice as likely' to have a low acuity presentation to the hospital ED, compared with low SES families. Both Williams et al 14 and Alele et al 15 used the Australian Bureau of Statistics Socio-Economic Indexes for Areas (SEIFA) data and postcode as a means of indicating SES. This is consistent with the international literature where postcode and census data have been used to develop indices that measure a community's level of deprivation.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…[20][21][22] Other reported factors, such as regular primary care follow-up and parental socioeconomic status, could not be examined in our study. [23][24][25] However, most children have regular paediatric follow-up in Switzerland. 4…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…Low-acuity paediatric emergency departments (PEDs) visits are frequent, constituting up to three-quarters of all PED visits. [1][2][3] Unscheduled medical consultations for non-life-threatening issues were traditionally provided by primary care providers in Switzerland. For children, paediatricians are the first-line providers of care with nearly 80% of all preschoolers regularly seeing a primary care paediatrician.…”
Section: Introductionmentioning
confidence: 99%